Interests and options of developing and least developed countries in a new round of multilateral trade negotiations - Oyejide, T. Ademola (UN New YorkUS, 2000)
Discusses the trade-strategy options of low-income countries, the areas of greatest interest to developing countries, as well as those that are to pose the greatest defficulties, the question of how developing countries can enhance the effectiveness of their participation in the hew round of Multilateral Trade Negotiations. Makes some suggesations on how to change WTO governance and management structures in order to ensure that the concerns of low-income members are given greater prominence in the organization's activities.